Efektivitas Media Infografis terhadap Keterampilan Menulis Teks Pidato Siswa SMP Negeri 55 Surabaya - Natasya Permata Dewi; Titik Indarti (STIKes Ibnu Sina Ajibarang, 2026)
This research is motivated by the low skills of students in writing speech texts, especially in the aspects of structure, idea development, and language use. This study aims to describe the application of infographic media, analyze the differences in writing abilities between the experimental and control classes, and determine student responses. The study used a quantitative approach with an experimental design at SMP Negeri 55 Surabaya. The research sample consisted of class VIII B as the experiment and VIII A as the control. Data collection techniques included observation, pretest and posttest tests, and questionnaires. Data analysis used descriptive statistics and independent sample t-test. The results showed that the application of infographic media ran very well. There was a significant difference in the ability to write speech texts between the two classes, with an average posttest score of 78.2 for the experimental class and 69.5 for the control class (sig. 0.000 <0.05). Student responses were also in the very good category. Thus, infographic media is effective in improving students' speech writing skills.